Nieistniejące istnienie. Uwagi o przyczynowaniu przedmiotu estetycznego - Kornacka-Sareło, Katarzyna (Studia Europaea Gnesnensia, 2025)
The paper examines an aesthetic object (work of art) as an intentional being. Also, it is approached as a product of intertextual practices or “games”. Thus, the existence of such an object is dependent on previous works of art as well as on the conscious acts of the reader who is able (or unable) to decode the hidden meanings and content of a work of art. It is also emphasized that the meanings cannot be precisely determined, since an aesthetic object exists dynamically, changing constantly through acts of creation and acts of interpreting. Such a theoretical approach is consistent with the mimetic theory formulated by Plato and Werner K. Heisenberg’s indeterminacy principle. Moreover, it is linked to the concept of “différance” formulated by Jacques Derrida.